2023
DOI: 10.1186/s12890-023-02335-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and factors associated with alexithymia among patients with chronic obstructive pulmonary disease in China: a cross-sectional study

Abstract: Background Alexithymia is a common psychological disorder. However, few studies have investigated its prevalence and predictors in patients with chronic obstructive pulmonary disease (COPD). Therefore, we aimed to determine the prevalence and predictors of alexithymia in Chinese patients. Methods This cross-sectional study included 842 COPD patients to assess the prevalence and predictors of alexithymia using the 20-item Toronto Alexithymia Scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
4
1
Order By: Relevance
“…These health conditions seem related to psychological distress. However, the results of univariate analysis showed these factors are not related to psychological distress, which is contrary to Zhang et al 50 . This disparity may be explained as follows: 1) limited sample size leads to an inapparent association; 2) the relationship between health conditions and psychological distress may be restricted by other factors; 3) when collecting data, the research population didn't fill in measurements carefully, which might present fatigue effect or social desirability bias.…”
Section: Exercise Frequencycontrasting
confidence: 78%
“…These health conditions seem related to psychological distress. However, the results of univariate analysis showed these factors are not related to psychological distress, which is contrary to Zhang et al 50 . This disparity may be explained as follows: 1) limited sample size leads to an inapparent association; 2) the relationship between health conditions and psychological distress may be restricted by other factors; 3) when collecting data, the research population didn't fill in measurements carefully, which might present fatigue effect or social desirability bias.…”
Section: Exercise Frequencycontrasting
confidence: 78%
“…Researchers also investigated the relationship between alexithymia and chronic obstructive pulmonary disease (COPD), noting that this variable is associated with anxiety, depression, and impaired quality of life ( Tselebis et al, 2010 ; Zhang et al, 2023 ), thus confirming the relevance of analyzing alexithymia in clinical settings.…”
Section: Discussionmentioning
confidence: 96%
“…According to different studies, alexithymia has been described as impacting, complicating, and often directly affecting the psychological condition of subjects ( Baiardini et al, 2015 ; Myles and Merlo, 2021 ). Selinheimo et al (2022) and Zhang et al (2023) highlighted a bidirectional influence between alexithymia and chronic respiratory diseases, and thus, reported that alexithymia increases the risk of developing chronic airway inflammation and vice versa. In the first study, subjects were followed for alexithymia for 11 years using binary logistic regressions to investigate the role of psychological factors in the onset and maintenance of physical conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The SGRQ score is an important indicator of quality of life in patients with chronic lung disease and can be used as an independent predictor of COPD combined with anxiety and depression [ 26 ]. The SGRQ score has now been widely used to assess quality of life in patients with IPF, and a higher SGRQ-T score implies a poorer quality of life.…”
Section: Discussionmentioning
confidence: 99%